1993
DOI: 10.1111/j.1399-302x.1993.tb00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of periodontopathogenic bacteria to killing by light from a low‐power laser

Abstract: Cultures of Porphyromonas gingivalis, Fusobacterium nucleatum and Actinobacillus actinomycetemcomitans were treated with a range of photosensitizers and then exposed to light from a 7.3 mW helium/neon laser for up to 80 s. Toluidine blue O (25 micrograms/ml) and methylene blue (25 micrograms/ml) were effective lethal photosensitizers of all 3 target organisms, enabling substantial light dose-related reductions in viable counts. Dihaematoporphyrin ester and aluminium disulphonated phthalocyanine were lethal pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
19

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 13 publications
3
71
0
19
Order By: Relevance
“…MB and TB are commercial phenothiazine dyes widely accepted in medical practice. The photobactericidal ability of these dyes against different pathogenic organisms including viruses, bacteria and yeasts has been repeatedly demonstrated in the literature [4][5][6][7]. From these studies and our own investigations it might be assumed that TB is a more lethal photosensitizer of bacteria and yeasts whereas MB exhibits a greater efficacy against viruses.…”
Section: Introductionmentioning
confidence: 80%
“…MB and TB are commercial phenothiazine dyes widely accepted in medical practice. The photobactericidal ability of these dyes against different pathogenic organisms including viruses, bacteria and yeasts has been repeatedly demonstrated in the literature [4][5][6][7]. From these studies and our own investigations it might be assumed that TB is a more lethal photosensitizer of bacteria and yeasts whereas MB exhibits a greater efficacy against viruses.…”
Section: Introductionmentioning
confidence: 80%
“…Photodynamic action has been used to kill oral microorganisms since the beginning of the 1990s, when studies demonstrated that some photosensitizers show affinity for bacterial walls and can be photoactivated to cause the desired damage [19][20][21] . Excited photosensitizer molecules can transfer energy to nearby molecules, resulting in the formation of reactive molecules as singlet oxygen, superoxide, and other free radicals, capable of causing damage and even death of cells and bacteria [22][23][24][25] .…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…18 After its successful implementation in medicine, research extended to the application of this therapy in the killing of oral bacteria, with many successful results in this fi eld against a wide scope of oral bacteria. [19][20][21][22][23][24][25][26][27][28][29] The mechanism of action of PAD therapy is governed by the interaction of a photosensitive antimi crobial agent and a selective laser light source. PAD therapy works by means of the formation of labile singlet oxygen or radicals, which trigger a cascade of redox reactions, the end result of which is the destruction of bacterial cells and their cellular components.…”
Section: Discussionmentioning
confidence: 99%